HUBUNGAN ANTARA KECERDASAN EMOSIONAL DAN KEMAMPUAN BERBAHASA INGGRIS PADA SISWA SMKN 3 BENGKULU - Bambang Suwarno; Alamsyah Harahap; Syahrial Syahrial (Universitas Bengkulu, 2016)
This study aims to explore the relationship between emotional intelligence and English proficiency among the students of SMKN 3 Bengkulu. The students were limited to classes XI and XII. The design was correlational research. The sample included 6 classes from each level. The instrument included a questionnaire of emotional intelligence and teacher-made tests. In data analysis, descriptive and correlational calculations were employed. It was found that the students’ mean of English proficiency was in the 'high' category while the mean for emotional intelligence was in the 'moderate' category. There was no significant correlation between English proficiency and emotional intelligence for each class as well as for the overall sample. It is suggested that followup studies be performed through the use of other emotional intelligence measure and different English tests or the exploration of other populations.Kata Kunci: Emotional intelligence, English proficiency